The legal nature of the parliamentary question in the British system. (An analytical study) - Altarawneh , Mohannad saleh (International Journal of Psychosocial Rehabilitation, 2020)
The parliamentary question in the British system is considered one of the most important constitutional means possessed by the legislative authority represented in the (House of Commons) in the face of the executive authority. This study aims to clarify what the question is Parliament and to analyze its legal dimensions, justifications, importance, types and legal procedures for its presentation, leading to a precise legal understanding of the parliamentary question In the British system. This study will attempt, through this context, to divide the topics of the parliamentary question into three topics: an introductory topic and two main topics. This study will address the explanation of what are the oral, written and urgent parliamentary questions. As for the third topic, the study will address the legal procedures for the way to present the types of questions mentioned above to the British House of Commons.